Pengembangan Lembar Kerja Siswa (LKS) Ilustratif Bermuatan Pendidikan Karakter Pada Pembelajaran Matematika SDN 01 Rejang Lebong - Zahratul Fitria; Syaripah Syaripah (AR-RIAYAH : Jurnal Pendidikan Dasar, 2020)
The background of this research was a phenomenon in the educational process where the teaching materials used were not optimal, so a development was needed. In this case, the teaching materials were Students Worksheets (LKS) used at SDN 01 Rejang Lebong and they only contained questions and exercises, without being equipped with the presentation of teaching material, character values and illustrative examples. This study aims to develop teaching materials in the form of illustrative Student Worksheets (LKS) containing character education in mathematics learning for grade 1 in the 2020/2021 academic year. This research was a type of development research with a 4D model (Define, Design, Develop and Disseminate). This research was conducted at SDN 01 Rejang Lebong. The subjects of this study were 16 students of class 1A. Data collection techniques in this study were: (1) observation, (2) interview, and (3) questionnaire. The data analysis technique was carried out using descriptive analysis with validation tests from 2 material experts and 1 media expert. The result of this research was the development of illustrative student worksheets (LKS) with character education in mathematics learning in grade 1 SDN 01 Rejang Lebong which produces a pre-content section with a main title page (cover), an identity page, an introduction, and a table of contents. The content section contains mathematics learning material on whole numbers. The closing section of the content contains a bibliography and author profile, with a total of 20 pages using A4 paper for the contents of Student Worksheets (LKS). The results of the feasibility assessment by material experts get an average score with a score of 4.15 which is in the right category. As well as the average number of scores with 4.2 from the media design experts getting an average number of scores with an average score in the right category.